HUBUNGAN ANTARA LAMA PEMBERIAN ASI EKSKLUSIF DENGAN PERKEMBANGAN ANAK USIA 12 - 36 BULAN - Sugeng Triyani; Nessi Meilan; Niken Purbowati (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
The merely giving breastfeedinguntilfour month of age,is the best step for the baby life."Then additional food which match with the need of various step of development that the child can achieve optimal level of development (Roesli, Utami, 2005)."In Indonesia giving breastfeeding at the age less than 2 months is 64%, between 2-3 months is 45.5%, between 4-5 months is 13.9%, and between 6-7 months is 7.8% (SDKI 2002). In Kenanga Posyandu RW 15 Pedongkelan Kayu Putih Jakarta Timur the giving breastfeeding is 70% unexclusively. The aim of this research is to look for the long of giving exclusive breastfeedingand the child development at the age 12-36 months.The research design usedis retrospective cohort study with cross sectional approach. The development of child detected by Kuesioner Pre-skrining Perkembangan (KPSP), than the parrents are given questioner about the length of giving brestfeeding exclusively. The samples of this research is 100 couple mothers and childern taken by random cluster sampling technique. Chi Square Testresault in significant relation between the length of giving breastfeeding exclusively ( p-value 0,000), with the development of child at the age 12-36 months. The conclusion is the longer giving breastfeeding exclusively the more optimal of child development at the age 12-36 months.